Numerical investigation on a double layer combined cooling structure for aerodynamic heat control of hypersonic vehicle leading edge. (25th March 2020) - Ding, Rui; Wang, Jianhua; He, Fei; Wang, Meng; Luan, Yun; Dong, Guangqi; Tang, Longsheng
Highlights: A novel thermal management technique named by double layer combined cooling is proposed. A coupled numerical method to study the comprehensive cooling performances is established. Characteristics of the system on controlling the non-uniform aerodynamic heat are analyzed. An improving strategy with a flexible and reasonable film slot layout is exhibited and tested. Abstract: A novel double layer combined cooling conception is suggested in this paper, i.e., an inner layer with discrete slots to allocate the coolant locally and an outer layer with homogeneous porous matrix to diffuse the coolant extensively. To investigate the cooling performances, mechanisms and improvements of the new structure, an entire-field-coupled numerical approach is established and validated by the experimental data obtained in an arc-heated wind tunnel under the supersonic conditions of Ma = 4.2, T0  = 2310 K and P0  = 1.33 MPa. Using the validated numerical approach, three interesting attempts are conducted: (1) The cooling characteristics of four slot-layouts (S1/S3/S5/S7) are systematically studied and compared at three coolant injection rates (30/40/50 g/s). (2) The comparison indicated that S3 can decrease the peak temperature most greatly even by 66.9% when Mc  = 50 g/s, hence it's chosen as the best design to investigate the cooling mechanisms in the entire region. (3) Based on the mechanism investigation, an improved design with a semi through-slot in the high temperature region is suggested, and the corresponding simulation predicated that this design can further reduce the coolant consumption by 20%. This work aims to provide the designers of future hypersonic vehicles with a valuable reference, to search for an active thermal management approach with high efficiency and low thermal stress.